Application of modular teaching combined with progressive cases in clinical nursing teaching of anorectal surgery (模块化教学结合进展性案例在肛肠外科临床护理教学中的应用研究) - LI Ping (李萍); XIE Wei (谢薇); SUN Lu (孙璐); FENG Lin (冯琳) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of modular teaching combined with progressive cases in clinical nursing teaching of anorectal surgery. Methods Totally 90 nursing students who participated in the internship in the Department of Anorectal Surgery were selected and divided into the control group and observation group according to the time of arrival, with 45 nursing students in each group. The control group received conventional clinical nursing teaching mode, while the observation group was given modular teaching combined with progressive cases teaching method. The outcomes of theoretical examination and practical skills assessment of two groups were compared. A questionnaire survey was adopted to evaluate the satisfaction with teaching method in the observation group. Results Scores of theoretical examination, practical skills and ward-round assessment of nursing students in the observation group were higher than those in the control group(P＜0. 01). Students in the observation group believed that modular teaching combined with progressive cases were effective to enhance the knowledge level and practice skills of anorectal surgery nursing, improve nursing students' learning initiative, clinical thinking, sense of teamwork and communication ability. Conclusion The application of modular teaching combined with progressive cases can effectively improve the performance and comprehensive ability of nursing students. (目的 研究模块化教学结合进展性案例在肛肠外科临床护理教学中的应用效果。方法 选取2022年医院肛肠外科实习护生90例, 根据实习时间先后分为对照组45例和观察组45例。对照组采取常规临床护理教学模式, 观察组选择模块化教学结合进展性案例临床护理教学模式。对比两组实习护生成绩, 评价观察组实习护生对模块化教学结合进展性案例的满意度。结果 观察组实习护生理论成绩、操作考核成绩、查房成绩均高于对照组, 差异有统计学意义(P＜0. 01)。观察组实习护生认为该种临床护理教学有助于理论知识、临床技能的掌握, 有助于提升学习积极性、临床思维能力、团队合作意识提升和沟通交流能力提升。结论 在肛肠外科临床护理教学中应用模块化教学结合进展性案例效果明确, 可以有效提升实习护士理论考核和实际操作成绩, 提升护生综合能力。)